Laser-modified charge-transfer processes in He2++H collisions. (15th September 2016) - Liu, C L; He, B; Zou, S Y; Wang, J G
Abstract: Laser-modified electron capture processes are studied for the He 2+ +H collision system in the low projectile energy region by solving the time-dependent Schrödinger equation. An obvious enhancement of the total and dominant state-selective charge-transfer cross sections are observed with respect to laser-free and weaker laser cases for low projectile energy. The influence of the laser pulse phase upon the cross sections is also studied and the reduction of the cross section is observed at some pulse phases with the increasing of the projectile energy. The time evolution for the dynamics of the collision system is analyzed in order to explore the dependence of the cross sections upon the pulse phase.